Analisis Perhitungan Harga Pokok Produksi dengan Metode Process Costing pada Usaha Bubur Ayam Cianjur Kang Ade - yoanna monica; rasyidah mustika; Randy Heriyanto; Endrawati (Politeknik Negeri Padang, 2022)
This study aims to analyze the calculation of the cost of goods manufactured using the Process Costing Method and presentation of profit/loss obtained at the Cianjur Kang Ade Chicken Porridge Business using the Full Costing Method for the period June 2022. The Cianjur Kang Ade Chicken Porridge Business is a company engaged in the manufacture which produces chicken porridge, yellow rice and uduk rice. In collecting research data, the method used was interviews conducted directly with the owner, and observation of the processes or activities contained within the company. After the research was completed, the cost of goods manufactured for each product was obtained in June 2022, namely chicken porridge Rp. 6,622/portion, yellow rice Rp. 6,089/portion, and nasi uduk Rp. 6,062/portion. In addition, the profit earned by Kang Ade's Cianjur Chicken Porridge Business for June 2022 amounted to IDR 23,173,009